Cytoplasmic HuR status predicts disease-free survival in resected pancreatic cancer - Tatarian, Talar; Büchler, Markus W. (Annals of surgery, 2018)
Objectives:We tested cytoplasmic HuR (cHuR) as a predictive marker for response to chemotherapy by examining tumor samples from the international European Study Group of Pancreatic Cancer-3 trial, in which patients with resected pancreatic ductal adenocarcinoma (PDA) received either gemcitabine (GEM